2010
DOI: 10.1246/bcsj.20090180
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity, Leachability, and Antimicrobial Activity of Poly(vinyl chloride) Blended with Benzyldimethyltetradecylammonium Bis(2-ethylhexyl) Sulfonatosuccinate

Abstract: Benzyldimethyltetradecylammonium (BA14 + ) salt with bis(2-ethylhexyl) sulfonatosuccinate (BEHS ¹ ) anion maintains its liquid state even at room temperature, so it can be regarded as a halogen-free low-volatile liquid material. In this study, the potential use of BA14BEHS as additive for poly(vinyl chloride) (PVC) has been investigated. The temperature dependence of the storage and loss moduli of PVC films blended with BA14BEHS showed a similar trend of that with a traditional plasticizer bis(2-ethylhexyl) ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…6,8,10,11,13 For ILs, two major factors are found to affect their thermal properties: 1) IL structure; for instance the length of the alkyl group and, cation and anion type; and 2) influence of the environment and impurities, such as heating rate, sample weight, apparatus and pan type, gas flow rate and the presence of oxygen. 13 While the thermal properties of PVC-IL samples have also been studied 7,8,10,11,14 , determination of their thermal degradation products has not. The endless possible combinations of IL cation and anion make it impossible to predict the thermal properties of particular ILs without detailed experiments, further complicated by the degradation mechanism and products of the polymer.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…6,8,10,11,13 For ILs, two major factors are found to affect their thermal properties: 1) IL structure; for instance the length of the alkyl group and, cation and anion type; and 2) influence of the environment and impurities, such as heating rate, sample weight, apparatus and pan type, gas flow rate and the presence of oxygen. 13 While the thermal properties of PVC-IL samples have also been studied 7,8,10,11,14 , determination of their thermal degradation products has not. The endless possible combinations of IL cation and anion make it impossible to predict the thermal properties of particular ILs without detailed experiments, further complicated by the degradation mechanism and products of the polymer.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This result was consistent with our previous result using a complex of the BEHS − anion and quaternary ammonium surfactant for polyvinyl chloride. 15 We did not test an antimicrobial activity of the PP film containing only ε-PL because the phase separation would impair a looking and mechanical property of the PP film (Figure S3). As for the PP film containing only NaBEHS, NaBEHS did not exhibit an antimicrobial activity against E. coli in a liquid culture medium (data not shown).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Here, we report on the preparation and availability of the water-insoluble complex formed by PL n + and the synthetic anionic surfactant, bis­(2-ethylhexyl) sulfosuccinate (BEHS – , is also commercialized as AOT) anion. Studies have demonstrated that the formation of a complex between BEHS – anion and a cationic compound, for example, poly­( N -ethyl-4-vinylpyridinium bromide), poly­(diallydimethylammonium chloride), and benzyldimethyltetradecylammonium, strongly suggesting that the BEHS – anion may also interact with PL n + . As expected, the water-insoluble complex was obtained, and the antimicrobial activity of the PL n + /BEHS – -complex, which is soluble in organic solvents, was investigated through coating a cellulose acetate membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The BA14BEHS and BA14BEHP maintain their liquid state even at room temperature, 21,22 and BA14BTA maintains its solid state. These salts are soluble in the OS's, such as 2-propanol (IPA), acetonitrile (AN), ethyl acetate (EA), tetrahydrofuran (THF), dichloromethane (DCM), and n-hexane (HEX ) anions, were prepared.…”
Section: D0→mentioning
confidence: 99%
“…The QAX salts can be added also to polymer materials. 22 Although studies concerning the coordination chemistry and the sensitization mechanism are needed, the application of the X --adduct of [Eu(FOD)3] as a red luminescent material is interesting. …”
mentioning
confidence: 99%